Implementation of the care agreements of the CACTO program for mothers of children with autism spectrum disorder - Paulo Roberto Lima Falcão do Vale; Jovana Gonçalves dos Santos; Rebecca de Azevedo e Silva; San Medrado Silva Andrade; Núbia Samara Caribé de Aragão; Luana Tonin; Rosely Cabral de Carvalho; Evanilda Souza de Santana Carvalho (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: to analyze the implementation of care agreements developed in the CACTO program for mothers of children with Autism Spectrum Disorder. Method: exploratory, qualitative study, guided by Unitary Caring Science and the Implementation Science methodological framework, based on the Consolidated Conceptual Framework for Implementation Research. Conducted with 20 mothers of children with Autism Spectrum Disorder, between April 2023 and February 2024, during care meetings developed in a non-governmental organization. For analysis, deductive thematic content analysis was used. Results: the agreements were categorized into three dimensions of human existence: body-mind-soul. The health needs of mothers determined the implementation of the agreements, such as: difficulties in body acceptance, sedentary lifestyle, lack of awareness of their own potential, insufficient self-care, unresolved past conflicts, self-blame, family conflicts, signs and symptoms of overload and fragility in the relationship with God. The lack of time and oppressive relationships were barriers, while motivation and spirituality served as strengths for the mothers in applying the agreement device. Final considerations: in-depth dialogue and the leading role of the mothers were decisive in the implementation of the agreements. Professional caregivers play a fundamental role in epistemological development while triggering innovative care in the health field.